1997
DOI: 10.1099/00221287-143-10-3137
|View full text |Cite
|
Sign up to set email alerts
|

Structural analysis of the 6 kb cryptic plasmid pFAJ2600 from Rhodococcus erythropolis NI86/21 and construction of Escherichia coli-Rhodococcus shuttle vectors

Abstract: The complete nucleotide sequence of the 5936 bp cryptic plasmid pFAJ2600 from Rhodococcus erythropolis N186/21 was determined. Based on the characteristics of its putative replication genes, mpA and mpB, pFAJ2600 was assigned to the family of pAL50OO-relatd small replicons identified in Mycobacterium (pAL5000), CorynebaCterium (pXZ10142), Brevibacterium (pRBLI), Bifidobacterium (pMB1) and Neisseria (pJD1). The replication systems of these plasmids show striking similarities to the ones used by the ColE2 family… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(49 citation statements)
references
References 65 publications
0
49
0
Order By: Relevance
“…The TnpA transposase of S. fradiae is the closest relative of R. ruber TnpA, with 49% identity. The orf5 product of S. fradiae Tn4556 is a potential resolvase of Tn4556 whose similarity with the R. ruber TnpR extends into the upstream region of this ORF, disregarding a TAG stop codon as mentioned by De Mot et al (6). The deduced polypeptide of 324 residues is 31% identical to TnpR of R. ruber.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…The TnpA transposase of S. fradiae is the closest relative of R. ruber TnpA, with 49% identity. The orf5 product of S. fradiae Tn4556 is a potential resolvase of Tn4556 whose similarity with the R. ruber TnpR extends into the upstream region of this ORF, disregarding a TAG stop codon as mentioned by De Mot et al (6). The deduced polypeptide of 324 residues is 31% identical to TnpR of R. ruber.…”
Section: Resultsmentioning
confidence: 81%
“…The deduced polypeptide of 324 residues is 31% identical to TnpR of R. ruber. The closest relative of R. ruber TnpR is R. erythropolis PmrA (62% identity), which is a site-specific recombinase of the integrase family and may be involved in stabilization of the cryptic plasmid pFAJ2600 (6). Amino acid comparisons revealed that other proteins related to R. ruber TnpR are almost exclusively sitespecific recombinases of the integrase family.…”
Section: Resultsmentioning
confidence: 99%
“…However, the mechanisms of plasmid replication, inheritance, and host ranges have not yet received much attention. The two replication proteins (RepA and RepB) found in most small plasmids of Nocardia, as well as those of the closely related Rhodococcus, resemble replication proteins of the theta-type replicating Mycobacterium plasmid pAL5000 (111,177,241). The replication protein of Nocardia plasmid pNI100 (308a) resembles the rolling-circle replication proteins encoded by the Streptomyces plasmids pIJ101 and pSG5 (238,277).…”
Section: Extrachromosomal Dna Elements In Nocardiamentioning
confidence: 99%
“…RHL3.237, designated rep1, encodes a 444-residue protein that shares up to 25% amino acid sequence identity with rep genes of mycobacterial and rhodococcal plasmids (3,5,16,46) (Table 1). RHL3.235 encodes a protein that shares 34% sequence identity to ParA protein from R. erythropolis (15). Both pJBG6 and pBTSBK contain rep1.…”
Section: Vol 186 2004mentioning
confidence: 99%